Solve for <span>yy</span> in <span>2x+y=20<span>2x+y=20</span></span>How? <span>y=20-2x<span>y=20−2x</span></span> Substitute <span>y=20-2x<span>y=20−2x</span></span> into <span>-5y=-6x+12<span>−5y=−6x+12</span></span>How? <span>-5(20-2x)=-6x+12<span>−5(20−2x)=−6x+12</span></span>
Solve for <span>xx</span> in <span>-5(20-2x)=-6x+12<span>−5(20−2x)=−6x+12</span></span>How? <span>x=7<span>x=7</span></span>
Substitute <span>x=7<span>x=7</span></span> into <span>y=20-2x<span>y=20−2x</span></span>How? <span>y=6<span>y=6</span></span> Therefore, <span>x=7<span>x=7</span></span> <span>y=6<span>y=6</span></span> <span> </span>